Analisis Semiotika Komunikasi Visual Brand Lafiye dalam Membangun Brand Image melalui Website - Afilika, Ganis Filma; Batubara, Abdul Karim (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study analyzes the visual communication strategy and brand image formation through multimodal elements on the Lafiye website. Using a qualitative approach with Roland Barthes' semiotic analysis, this research examines brand identity representations across the homepage, product pages, and the